Karakteristik Penerimaan Konsumen Dan Mutu Kerupuk Siput Bakau (Terebralia sulcata) - Sumarto, Sumarto; Sujoko, Sujoko (Jurnal Perikanan dan Kelautan, 2010)
This research conducted to determine the level of consumer acceptance andquality by organoleptic and chemical on mangrove snail crackers (Terebralia sulcata)with different utilization level of meat. Results showed that the addition of mangrovesnail meat affect the level of consumer acceptance, and the highest consumer acceptanceis 78% on crackers with the addition of 30% mangrove snail meat, which significantlyaffect the characteristics of organoleptic quality, flower power and chemical. The besttreatment is the addition of 30% mangrove snail meat with organoleptic qualitycharacteristics are interesting sightings crackers, typical colors (brownish white), typicalsmelly mangrove snail meat and no smell distorted, compact and crunchy texture,distinctive taste of mangrove snail crackers very tasty and delicious. Flower power of themangrove snail crackers reaches 98.29%, with characteristic chemical quality 9.91%water, 9.26% protein, 1.03% fat, 0.92% ash and 198 mg calcium.